2003
DOI: 10.3168/jds.s0022-0302(03)73907-1
|View full text |Cite
|
Sign up to set email alerts
|

Inactivation of Spores of Bacillus cereus in Cheese by High Hydrostatic Pressure with the Addition of Nisin or Lysozyme

Abstract: The objective of this work was to study high hydrostatic pressure (HHP) inactivation of spores of Bacillus cereus ATCC 9139 inoculated in model cheeses made of raw milk, together with the effects of the addition of nisin or lysozyme. The concentration of spores in model cheeses was approximately 6-log10 cfu/g of cheese. Cheeses were vacuum packed and stored at 8 degrees C. All samples except controls were submitted to a germination cycle of 60 MPa at 30 degrees C for 210 min, to a vegetative cells destruction … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
60
0
3

Year Published

2007
2007
2017
2017

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 126 publications
(69 citation statements)
references
References 21 publications
6
60
0
3
Order By: Relevance
“…Previous studies reported that nisin prevented the growth of Bacillus spores derived from several different species (4,14,32,35,43). To evaluate the action of nisin against spores responsible for this inhibitory activity, spores were prepared from B. anthracis Sterne 7702, which is a strain commonly employed as a model for investigation of the early stages of anthrax disease (24,47 Table 1).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Previous studies reported that nisin prevented the growth of Bacillus spores derived from several different species (4,14,32,35,43). To evaluate the action of nisin against spores responsible for this inhibitory activity, spores were prepared from B. anthracis Sterne 7702, which is a strain commonly employed as a model for investigation of the early stages of anthrax disease (24,47 Table 1).…”
Section: Resultsmentioning
confidence: 99%
“…In this study, B. anthracis was used as a model, but previous work indicated that nisin is also inhibitory against spores from other Bacillus species (3,7,30,32,35,43), as well as from Clostridium species (36), suggesting that the new information on the inhibitory activity of nisin obtained in this study will be applicable to determination of the mechanism of action of nisin against spores from these other organisms as well. Here, nisin was demonstrated to act upon and kill germinated spores of B. anthracis prior to development into elongated and dividing bacilli and before LT was generated.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Of note, the anti-HIV activity of lysozyme is independent of its muramidase activity (5). In addition, findings of previous studies have shown that it is effective in inactivating spores of Bacillus cereus in cheese by causing high hydrostatic pressure following the addition of lysozyme (6).…”
Section: Introductionmentioning
confidence: 90%
“…Hücre için önemli enzimlerin denatüre olması ve ribozomun zarar görmesi mikroorganizmanın inaktivasyonuna neden olmaktadır [101]. Nisinin HHP uygulaması ile birlikte gösterdiği sinerjistik antimikrobiyel etki ise söz konusu iki engelin hücre zarında meydana getirdikleri kümülatif hasardan ileri gelmektedir [102,106]. HHP uygulamasının antimikrobiyel etkinliği uygulanan bakteri popülasyonunun özelliklerine ve hücrelerin bulundukları gelişim evrelerine göre değişkenlik gösterir.…”
Section: Nisinin Fiziksel İşlemlerle Birlikte Kullanımıunclassified